Yield enhancement strategies for the production of picroliv from hairy root culture of Picrorhiza kurroa Royle ex Benth. - Verma, Praveen Chandra (Plant Signal Behav, 2015)
Fast-growing hairy root cultures of Picrorhiza kurroa induced by Agrobacterium rhizogenes offers a potential production system for iridoid glycosides. In present study we have investigated the effects of various nutrient medium formulations viz B5, MS, WP and NN, and sucrose concentrations (1–8%) on the biomass and glycoside production of selected clone (14-P) of P. kurroa hairy root. Full strength B5 medium was found to be most suitable for maximum biomass yield on the 40th day of culture (GI = 32.72 ± 0.44) followed by the NN medium of the same strength (GI = 22.9 ± 0.43). Secondary metabolite production was 1.1 and 1.3 times higher in half strength B5 medium respectively in comparison to MS medium. Maximum biomass accumulation along with the maximum picroliv content was achieved with 4% sucrose concentration in basal medium. RT vitamin and Thiamine-HCl effected the growth and secondary metabolite production of hairy roots growing on MS medium but did not show any effect on other media. The pH of the medium played significant role in growth and secondary metabolite production and was found to be highest at pH 6.0 while lowest at pH 3.0 and pH 8.0. To enhance the production of biomass and Picroliv 5 liter working capacity bioreactor was used, 27-fold (324 g FW) higher growth was observed in bioreactor than shake flask and secondary metabolite production was similarly enhanced.